Maintenance Notes to Improve the Reliability of Wheel Flange Failure for Overhead Crane - Burhanuddin, Fakhri; Yuwono, Akhmad Herman (Journal of Materials Exploration and Findings, 2024)
Overhead traveling cranes in the industry have utility workload classifications and require high standards of safety and reliability by mobilizing lifting and transporting capacity variants of steel products, equipment, and other supports. The crane wheels are the main support in moving the end carriage so that the crane can work according to its function. Failures in the operation and maintenance cycle have occurred. Therefore, proper repair and maintenance methods are highly needed to restore the original design function to its working integrity. Logic tree analysis was used to breakdown all causes of failure; thus, mitigation was performed by carrying out continuous improvements rather than investigations. In this work, failure of the wheel flange in asset integrity management was found to be correlated with other related components which refer to the data of international standard for carrying out the needed repairs.